2003
DOI: 10.1046/j.1365-2915.2003.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the predation rate of freshwater cyclopoid copepod species on larvae of the mosquito Culex pipiens

Abstract: The predation rates of six copepod species: Acanthocyclops robustus G.O. Sars, Eucyclops neumani Pesta, Macrocyclops albidus Jurine, Mesocyclops longisetus Thibaud, Metacyclops grandis Kiefer and Metacyclops mendocinus Wierzejski (Copepoda: Cyclopidae) on mosquito larvae, Culex pipiens Linnaeus (Diptera: Culicidae) were assessed. Experiments consisted of 24-h incubations of one copepod and 10 larvae without extra food at 16 degrees C and 26 degrees C. Nine replicates were considered for each species and temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…Crustaceans and some mollusc species have been investigated for candidate oviposition attractants of mosquitoes. The copepod species Mesocyclops longisetus , which previously was used for the biological control of mosquitoes (Calliari et al 2003), has been found to attract gravid Ae. aegypti .…”
Section: Principal Oviposition Chemical Signalsmentioning
confidence: 99%
“…Crustaceans and some mollusc species have been investigated for candidate oviposition attractants of mosquitoes. The copepod species Mesocyclops longisetus , which previously was used for the biological control of mosquitoes (Calliari et al 2003), has been found to attract gravid Ae. aegypti .…”
Section: Principal Oviposition Chemical Signalsmentioning
confidence: 99%
“…In the present study, one bioassay was performed with this species, resulting in 30 killed larvae out of 50 within 24 h. In bioassays conducted before the taxonomic revision, A. robustus predated a mean of four out of ten larvae of Culex pipiens s.l. per day, both at 16° C and at 26° C (Calliari et al ). Acanthocyclops vernalis killed a mean of 33±3 out of 50 larvae of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…All assays were carried out in the laboratory at 26±2° C (monitored by a data logger with ±0.5° C accuracy). We chose this temperature because predation at 26° C was higher than at 16° C (Calliari et al ) and at the same time is the optimal temperature for Ae. japonicus rearing in the laboratory (Reuss et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Simple protocols for culturing copepods species have been established for maintenance and mass propagation prior to release [36]. In laboratory studies, Mesocyclops species have also been demonstrated to prey on larvae of Anopheles and Culex species mosquitoes [37,38,39,40]. However, the majority of applications are still focused on the control of Ae.…”
Section: Predators For Mosquito Control—historical and Ongoing Stomentioning
confidence: 99%